PELATIHAN MITIGASI BENCANA BADAI UNTUK SISWA – SISWI DI SDN BOHAR KABUPATEN SIDOARJO - Muhammad Reza Ishadi Fadillah; Andharu, Devito; Wahyu Widayati; Isro Ani Widayati (Politeknik Negeri Sriwijaya, 2024)
The partner of this community service activity is SDN Bohar Sidoarjo Regency which is located at Jl. Raya Bohar No. 96, Balun, Bohar, Taman Subdistrict, Sidoarjo Regency, East Java. The principal of SDN Bohar is trying to conduct hurricane disaster mitigation training for students at the school. So the partner problems, in this case SDN Bohar Sidoarjo Regency, namely : 1) Students' understanding of disasters; 2) Students do not have insight and knowledge regarding hurricane disasters, so they need training regarding how to deal with disasters. The short-term goal of community service activities is to increase students' knowledge and abilities by providing training on disaster mitigation materials. Apart from that, it also develops links and matches between DR. Soetomo University and SDN Bohar. The implementation methods used in community activity programs include 1) training, there are two stages of training, namely, training on basic disaster concept material; 2) Training on hurricane disaster mitigation by inviting a moispena car from the East Java BPBD. The results of this community service activity are: 1) There are significant differences before and after the training, before and after the basic concepts of disaster mitigation are explained, this can be seen from the students' ability to understand disaster hazards; 2) During the hurricane disaster mitigation training process, partners and service teams work together so that the specified targets can be implemented well.